2012
DOI: 10.1097/hmr.0b013e31822af831
|View full text |Cite
|
Sign up to set email alerts
|

All teach, all learn, all improve?

Abstract: Background-Quality improvement collaboratives are an increasingly common strategy for implementing evidence-based practices in health care. However, research shows that many participating organizations do not achieve the level of performance improvement desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…By sharing both successes and failures, teams were able to learn valuable dos and don’ts and consider practices that might be worthy of adopting as part of their QI efforts [6]. In our study, participants identified that value of having opportunities to provide and receive both formal, structured and informal feedback.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By sharing both successes and failures, teams were able to learn valuable dos and don’ts and consider practices that might be worthy of adopting as part of their QI efforts [6]. In our study, participants identified that value of having opportunities to provide and receive both formal, structured and informal feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Fundamental to a collaborative approach is interorganizational learning whereby organizations acquire, share and combine knowledge with other organizations and have the opportunity to learn from the successes and failures of their peers in improvement areas [6]. This learning approach aims to create the conditions for collaborative, reflective, and innovative experiential systems that enable collective discussions regarding daily practice issues and finding solutions for improvement by integrating tacit-explicit knowledge [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…As health reform unfolds and primary care practices are expected to integrate routine health behavior assessment, practices will be faced with a need to revamp their patient-reported data collection processes. Technical assistance in the form of training on the use of behavioral health assessments, practice facilitation (Nutting et al 2010), structured rapid cycle quality improvement support (Rubenstein et al 2010), and interorganizational learning opportunities (Nembhard 2012) may aid practices in using PRO data and disseminating best practices in supporting patient health behavior change in low-resource settings. Unless implementation support is provided to practices, the routine collection and meaningful use of behavioral health data will likely flounder, particularly in low resource practices that serve the most vulnerable patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…This process allows teams to refine new practices within the local setting, identify implementation barriers, field test solutions to identified challenges, and share experiences across sites (Pinto, Benn, Burnett, Parand, & Vincent, 2011). At the organizational and systems level, LCs have potential to strengthen social networks and interorganizational learning (Bunger et al, 2014; Nembhard, 2012; Palinkas et al, 2011), leverage the influence of key opinion leaders towards improving the implementation climate for innovative practices (Wilson, Berwick, & Cleary, 2004), and foster a public and tanglible commitment from leadership (Wilson et al, 2004). By establishing mutli-disciplinary, cross-hierarchical teams, LCs may also promote increased team effectiveness (Nembhard, 2009), and can potentially build organizations’ capacity for innovation use and continuous improvement (e.g., using data to drive change and promote accountability) (Nembhard, 2012; Singer, Moore, Meterko, & Williams, 2012).…”
mentioning
confidence: 99%